2020
DOI: 10.2196/preprints.24544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Growth of Ambulatory Virtual Visits and Differential Use by Patient Sociodemographics at One Urban Academic Medical Center During the COVID-19 Pandemic: Retrospective Analysis (Preprint)

Abstract: BACKGROUND Despite widespread interest in the use of virtual (ie, telephone and video) visits for ambulatory patient care during the COVID-19 pandemic, studies examining their adoption during the pandemic by race, sex, age, or insurance are lacking. Moreover, there have been limited evaluations to date of the impact of these sociodemographic factors on the use of telephone versus video visits. Such assessments are crucial to identify, understand, and address differences in care delivery… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Our findings indicate that telephone and video assessments were not feasible for some patient populations, such as those with cognitive impairment, since care coordinators expressed concerns that these patients lacked insight about their own needs and risks. Similar findings have been shown comparing ability to complete video versus phone assessments in ambulatory care for older patients [24]. Utilization barriers among older adults, including visual and auditory sensory deficits, technical literacy, mental acuity, and lack of technical support have been previously documented [25].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our findings indicate that telephone and video assessments were not feasible for some patient populations, such as those with cognitive impairment, since care coordinators expressed concerns that these patients lacked insight about their own needs and risks. Similar findings have been shown comparing ability to complete video versus phone assessments in ambulatory care for older patients [24]. Utilization barriers among older adults, including visual and auditory sensory deficits, technical literacy, mental acuity, and lack of technical support have been previously documented [25].…”
Section: Discussionsupporting
confidence: 67%
“…This study received ethics approval from Brock University in August 2021 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). For the survey, voluntary participation implied informed consent when entering the Qualtrics survey.…”
Section: Ethicsmentioning
confidence: 99%
“…It has only been in the past several months that we have begun to see more publications highlighting the inequities that have been observed with rapid telemedicine rollouts across urban health care organizations. 17 18 Many of those studies have identified the areas of need for future research, advocacy, and consideration. To our knowledge, when this article was initially written this is the first study that outlines an evidence-based roadmap to more equitable telemedicine access.…”
Section: Discussionmentioning
confidence: 99%